Bad bets: Nonlinear incentives, risk, and performance - de Figueiredo, Rui J. P.; Rawley, Evan; Shelef, Orie (Strategic Management Journal, 2023)
Abstract Research Summary This article examines the consequences of incentive slope and shape on performance and risk‐taking. It focuses on how slope—incentive intensity—influences risk‐taking, and how shape—nonlinearity—influences performance. We use quasi‐random variation in the context of the hedge‐fund industry to separate slope and shape effects. Our results demonstrate that shape has large and important effects on performance, and that slope affects risk‐taking. The evidence suggests that poor performance in the industry is often due to bad bets—excessive risk‐taking that reduces performance—taken in response to nonlinear incentives. The findings suggest that, although nonlinear incentives are widely used, they can, under certain circumstances, predictably produce pernicious effects on organizational performance. Managerial Summary This article examines how nonlinear incentive contracts—such as contracts that reward performance above a threshold substantially more than below it—influence managerial behavior. Using the hedge‐fund industry, in which nonlinear incentives are ubiquitous, as a laboratory, we find that nonlinear incentive schemes cause managers who are “close” to, but below, the performance threshold to take bad bets—excessive risk‐taking that reduces performance. The findings suggest that, although nonlinear incentives are widely used, they can, under certain circumstances, predictably produce pernicious effects on organizational performance.